Two decades of changes in spatial distribution of retail and commercial services: Czech experience - Zdeněk Šilhan; Josef Kunc (Hungarian Geographical Bulletin, 2020)
The aim of this paper is to introduce basic developmental consequences, changes, trends and the current situation in amenities through retail and commercial services in the rural areas of the Czech Republic. The example illustrated herein is the South Moravian Region. Methodically, the text is built on previous survey (2002), and on our own survey conducted in municipalities up to 3,000 inhabitants of the South Moravian Region in 2018 (n = 355). There are semi-structured interviews (n = 18) that link back to these surveys. The data obtained was processed by the methods of statistical and graphical analysis, comparison, interpretation and synthesis. The paper concludes that since 2002, commercial amenities have experienced remarkably negative development. The smaller municipalities in the periphery have encountered the greatest decline, but stagnation is also seen in the suburban areas of Brno. From among types of commercial amenities, the ones most weakened were specialized shops, which could no longer compete with large retail chains. Almost a fourth of municipalities support commercial trade and services, mainly through subsidies or lowered rent. The regions also provide subsidies. Even simplifying red tape or providing tax relief on the part of the public sector would support civic amenities. Another key may be retaining young and educated people in municipalities where they will live and work. Contributing to this could be not only developing infrastructure in municipalities, but also for example the next wave of digitalization and introduction of stable, high-speed Internet service in rural areas.